2016
DOI: 10.1159/000446236
|View full text |Cite
|
Sign up to set email alerts
|

Chorioamnionitis and Five-Year Neurodevelopmental Outcome in Preterm Infants

Abstract: Background: Chorioamnionitis, a risk factor for preterm delivery, has been suggested to be associated with suboptimal neurological development in premature infants. Objective: To evaluate the association between chorioamnionitis and neurodevelopment in preterm infants at 5 years of age. Methods Very low birth weight and very low gestational age infants (n = 197) were recruited. Placental samples (n = 117) were evaluated for histological chorioamnionitis. Fetal histological chorioamnionitis was analyzed as a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…119 Yliloki et al recently reported the lack of association between CCA and neurodevelopmental problems in very preterm infants. 120 In contrast, HCA was associated with a slightly less optimal performance at 5 years of age, although, in their opinion, further studies are needed to verify the clinical significance of these findings. Previously, in a systematic review by the same group that included 84 original papers, they concluded that the majority of the studies did not support the hypothesis that CA poses a direct risk on the central nervous system of preterm infants.…”
Section: Brain Injurymentioning
confidence: 87%
“…119 Yliloki et al recently reported the lack of association between CCA and neurodevelopmental problems in very preterm infants. 120 In contrast, HCA was associated with a slightly less optimal performance at 5 years of age, although, in their opinion, further studies are needed to verify the clinical significance of these findings. Previously, in a systematic review by the same group that included 84 original papers, they concluded that the majority of the studies did not support the hypothesis that CA poses a direct risk on the central nervous system of preterm infants.…”
Section: Brain Injurymentioning
confidence: 87%
“…FIRS is associated with high rates of long-term morbidities such as cerebral palsy and developmental delay. 19–22 But a recent report by PIPARI study collaborators 23 suggests that clinical chorioamnionitis does not have a major independent role in the pathogenesis of neurodevelopmental problems in very preterm infants. The authors 24 argue that rather than chorioamnionitis other underlying pathologies behind preterm delivery may be contributory to preterm brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…This disorder is a tremendous burden on society and families. Studies show that maternal chorioamnionitis[ 15 ], maternal preeclampsia[ 16 ], maternal age >35 years, a low Apgar score at 5 minutes, preterm birth[ 17 ], low birth weight, periventricular/intraventricular hemorrhage[ 18 ], and bronchopulmonary dysplasia (BPD) are associated with CP. Among recent studies focusing on the relationship between maternal obesity and CP in offspring[ 9 , 12 , 13 , 17 , 19 22 ], two studies showed that maternal weight during pregnancy is associated with CP in offspring[ 23 , 24 ], and other studies indicated a significant association between maternal obesity and CP in children[ 9 , 12 , 13 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%